2017
DOI: 10.3389/fcimb.2017.00315
|View full text |Cite
|
Sign up to set email alerts
|

Lipopolysaccharide Upregulated Intestinal Epithelial Cell Expression of Fn14 and Activation of Fn14 Signaling Amplify Intestinal TLR4-Mediated Inflammation

Abstract: TLR4 in intestinal epithelial cells has been shown both inflammatory and homeostatic roles following binding of its cognate ligand lipopolysaccharide (LPS). TWEAK-Fn14 axis plays an important role in pathologies caused by excessive or abnormal inflammatory responses. This study aimed to evaluate potential cross-talk between TLR4 and TWEAK/Fn14 system in porcine small intestinal epithelial cells. Our in vivo results showed that, compared with the age-matched normal control piglets, increased expression of Fn14 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…Protein homogenates from goat PBMC were extracted as previously described [ 24 ]. Briefly, the cells were lysed for 20 min on ice in ice-cold lysis buffer (4906837001, Roche).…”
Section: Methodsmentioning
confidence: 99%
“…Protein homogenates from goat PBMC were extracted as previously described [ 24 ]. Briefly, the cells were lysed for 20 min on ice in ice-cold lysis buffer (4906837001, Roche).…”
Section: Methodsmentioning
confidence: 99%
“…It is well known that TLR4 recognizes LPS, a major component of the gram-negative bacterial cell wall. Increased TLR4 expression was induced by LPS in the porcine intestinal epithelial cell (Qi et al, 2017). A previous study indicated that mRNA abundance of jejunal TLR4 was decreased and intestinal injury was alleviated in weanling pigs supplemented with glutamate (Qin et al, 2018).…”
Section: Discussionmentioning
confidence: 90%
“…Because Fn14 is expressed in both nonhematopoietic (intestinal epithelial cells) 27 and hematopoietic (immune cells) 18 populations, we quantified separately the contribution of Fn14 that is derived from either cellular compartment in the development of chronic intestinal inflammation. In particular, we generated 4 groups of bone marrow (BM) chimeras that expressed either: (1) no components of the Fn14 receptor (knockout [KO] > KO mice); (2) only hematopoietic-derived Fn14 receptors (WT > KO mice); (3) only non–hematopoietic-derived Fn14 receptor (KO > WT mice); or (4) both hematopoietic and non–hematopoietic-derived Fn14 receptors (WT > WT mice) (Figure 4 A ).…”
Section: Resultsmentioning
confidence: 99%